Tim Whitmarsh, The Second Sophistic (Greece & Rome. New Surveys in the Classics), Oxford, Oxford University Press, 2005, 106 pp. (Minerva. Revista de Filología Clásica, 2019)
Reseña de Tim Whitmarsh, The Second Sophistic (Greece & Rome. New Surveys in the Classics), Oxford, Oxford University Press, 2005, 106 pp.